Strategi Komunikasi dalam Pembinaan Pecandu Narkoba dengan Pendekatan Therapeutic Community di Yayasan Sekata - Faisal, Muhammad; Juwita, Rina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This research looks at the persuasive communication strategies used by the Sekata Foundation in fostering drug addicts with the Therapeutic Community approach. This research aims to find out about what kind of communication strategies are used, what messages are conveyed, and what kind of approach is used by the Sekata Foundation in terms of coaching drug addict patients. This type of research is a descriptive qualitative research. The data collection methods used are interviews, observation and documentation. The data analysis techniques used are collecting data, reducing data, presenting data and drawing conclusions. The results showed that Sekata Foundation, in fostering drug addicts with the Therapeutic Community approach, uses a persuasive communication strategy. The purpose of this communication is to change attitudes, opinions, and behaviors. The communication strategies used tend to be effective in fostering drug addicts at Sekata Foundation in changing behavior, attitudes, and views.